Aplicación de la técnica de los mapas conceptuales para mejorar la comprensión de textos escritos en los alumnos de 1° año de Educación Secundaria de la I.E. N° 80819 “Francisco Lizarzaburu”, en El Porvenir, 2018 - Gavidia Casanova, Natalia Carolina (2018)
The present research work has the purpose of improving the comprehension of written texts of the first year students of secondary education of the I.E. N ° 80819 "Francisco Lizarzaburu", in the district of El Porvenir in 2018._x000D_ The population was 45 students and the sample was the same as that of the population to whom the measurement instruments were applied._x000D_ The procedures used were those provided by statistics, starting with the construction of tables, construction of graphs and the application of the statistical test of hypothesis testing to test the research hypothesis._x000D_ It was determined in the students, that 53.3% of them obtained a good level in the post test after the application of the technique of conceptual maps; finally determining that there is a significant difference between the scores obtained in the post test and those obtained in the pretest in comprehension of written texts (p <0.05), as a result of the application of the technique of conceptual maps._x000D_ It was concluded that the application of the concept map technique significantly influences the comprehension of written texts in first year secondary school students in the I.E. N ° 80819 "Francisco Lizarzaburu" in the district of El Porvenir in 2018.